Effectiveness of Music as a Medium for Environmental Conservation and Awareness Among Children at Kampoeng Baca Pelangi in Mercekebon Village, Narmada Subdistrict, West Lombok Regency - Yunan, Tegar La Nendar Amukti Prihatin; Permana, Beny; Junaidi, junaidi (Gema Cendekia Institute, 2024)
This research is motivated by the effective use of music as a medium for environmental conservation and awareness. The works created by the children of Kampoeng Baca Pelangi have made efforts to voice the importance of environmental conservation and awareness. The focus of this research is to understand the effectiveness of music as a medium for character building in environmental awareness among the children of Kampoeng Baca Pelangi in Mercekebon Village, Narmada Subdistrict, West Lombok Regency. This research uses a descriptive qualitative approach, a method that provides an overview and description of all activities using music as a medium to convey messages to children to understand the importance of preserving the natural environment. The research consists of four stages: planning, observation, implementation, and reflection. The research was conducted over a period of three months, emphasizing music as an effective medium for the children in the Kampoeng Baca Pelangi community in Mercekebon Village, Narmada Subdistrict, West Lombok Regency. The results of the research show that music can be an effective medium for raising community awareness about the environment and nature. This has proven to be effective for the children of Kampoeng Baca Pelangi. This is evidenced by the observed changes in the children's discipline in maintaining the cleanliness of their surroundings, their habit of disposing of waste properly, and their growing understanding of the importance of preserving the environment and nature for their future.